-28=12+2z

Simple and best practice solution for -28=12+2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28=12+2z equation:


Simplifying
-28 = 12 + 2z

Solving
-28 = 12 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
-28 + -2z = 12 + 2z + -2z

Combine like terms: 2z + -2z = 0
-28 + -2z = 12 + 0
-28 + -2z = 12

Add '28' to each side of the equation.
-28 + 28 + -2z = 12 + 28

Combine like terms: -28 + 28 = 0
0 + -2z = 12 + 28
-2z = 12 + 28

Combine like terms: 12 + 28 = 40
-2z = 40

Divide each side by '-2'.
z = -20

Simplifying
z = -20

See similar equations:

| (2-x).5=10 | | ln(1+x)-lnx=.25 | | -5x-10=5x | | 4(6x+7)=-40+7x | | 6x+15=9x+13-5x | | 16+4r=8(2+7r) | | 8y+6=3x | | 16x^2+3x+1=0 | | x+(x+1)=380 | | 8-6x-x^2=6+x | | -3h-5=-3h | | 9z-5-4z=5z | | 4(-6+p)=0 | | seag(X)=-4.2 | | -5(2-x)=5 | | 22(7-v)+10v=46 | | 3x-3(-3x+31)=39 | | 2x=(x-10)+40 | | e/20=6/15 | | 2(-8+x)=26 | | 4x-102=-10x+90 | | 1/2x-25=3 | | x+3y(-5x)=-28 | | 0.70x+24=1.19x | | 18x+88=-72+22x | | 3x-5+13=2x+11-8 | | 7(1+4n)=-33+8n | | 2.5x+0.4y=-14.1 | | 1/4x=-4.8 | | 86-21x=-106-18x | | 4cos^3x-2cos^2x-2cosx=2 | | 2x^2-3x+1=x^2-3x+2 |

Equations solver categories